Perceptions of selected low-income Filipino families on domestic comfort in relation to their residential interior spaces in a low-cost housing development - Francisco, Ma. Concepcion C.; Mayo, Adelaida V. (Quezon City College of Home Economics, University of the Philippines Diliman, 2018.)
This research assessed how low-income Filipino families living in low-cost housing units achieve domestic comfort despite the limitations of their residential interior spaces. It identified the respondents' background, investigated the interiors of their housing unit, assessed any design changes, analyzed their perceptions of domestic comfort and recommended interior design strategies. The research used a multiple-case study approach, conducted through two non-propability sampling stages. Using an interview guide pertaining to the family's background, a separate interview guide on their perception on domestic comfort and phone camera, data was gathered from an ocular visit, field observations, face-to-face interviews and photo documentation of the site. Even if all families have renovated their housing unit, common problems remained such as cramped spaces, an extremely warm atmosphere and excessive clutter. They describe a "comfortable" space as that which is cool in atmosphere, pleasing to the eye and clear or refreshing. This reiterates the theoretical framework, Witold Rybczynski's Onion Theory of Comfort, which identifies "layers of meaning" such as "convenience," "ease," and "pleasure," that define comfort. However, the research did discover another "layer" that is characteristic of the household heads' perception of domestic comfort that is psychological in nature- "Parental love." For future improvements, the researcher suggests to reuse, reduce, recycle and repurpose to address the cramped space and clutter as well as to use insulating materials to ease the heat they experience.
Thesis (B.S. Interior Design)--University of the Philippines Diliman
Keywords: Row houses -- Philippines; Row houses -- Philippines -- Psychological aspects